Predictors determining the duration of the hospital stay among patients admitted with single fractures - Joseph, Nitin; Hegde, Atmananda; Sachdeva, Dhruv; Mehta, Nishant; Arora, Kartik; Pahwa, Lavleen (Revista Cubana de Ortopedia y Traumatología, 2022)
Introduction: Fractures pose a tremendous burden on the health care systems due to the prolonged duration of admission. Addressing various determinants that prolong hospital stay will help minimize the cost of treatment. Objective: To study the determinants associated with the duration of hospital stay among patients admitted with fractures. Methods: This was a retrospective observational study conducted at a private tertiary care hospital in Mangalore. A semi-structured proforma was used for collecting data from the medical records. Results: The mean age of the 124 patients were 48.3±21.4 years. The majority were males [69(55.6%)] and were from urban areas [86(69.4%)]. Co-morbidities were present among 69(55.6%) patients. Out of the total patients, 8(6.4%) were alcoholics, and 10(8.1%) were tobacco smokers. The majority [50(40.3%)] had fracture of the femur. Five(4%) patients developed complications during the post-operative period. Seventy-eight (62.9%) patients had medical insurance facilities. The mean duration of hospital stay was 9.6±3.2 days among the patients. The mean duration of hospital stay among patients (n=115) before surgery was 2.4±1.6 days. Increased pre-operative stay, increasing age, rural residential status, open type of fracture, and being given general anesthesia for the operative procedure were significant predictors determining the period of stay among patients in the hospitals. Alcoholic status independently influenced the period of stay in the pre-operative period. Conclusion: Both patient and treatment characteristics were important determinants associated with the duration of hospital stay. Targeting these predictors will help to manage in-patients better and shorten their duration of hospital stay.